PIE LTER zooplankton surveys using plankton tows along transects in the Plum Island Sound estuary, Massachusetts (Reformatted to the ecocomDP Design Pattern) - Anne Giblin; Peter Milligan; Charles Hopkinson; Plum Island Ecosystems LTER (Environmental Data Initiative, 2021)
This data package is formatted as an ecocomDP (Ecological Community Data Pattern). For more information on ecocomDP see https://github.com/EDIorg/ecocomDP. This Level 1 data package was derived from the Level 0 data package found here: https://pasta.lternet.edu/package/metadata/eml/knb-lter-pie/405/2. The abstract below was extracted from the Level 0 data package and is included for context: Zooplankton were collected in spring and late summer/fall at four stations representing the salinity gradient in the Parker River-Plum Island Sound estuary. Two size classes,  greater than 335 micron and greater than 150 micron, were collected by net tows. Conductivity or salinty and temperature were recorded for each sample. Samples were concentrated to less than 250 mls and preserved in 70 percent EtOH. For taxonomy, sample splits were taken such that a minimum of 250 individuals were present, and counted under a dissecting microscope. Individuals were identified to the lowest taxonomic level possible, generally to species. Adult copepods were additionally characterized by sex. The Plum Island Ecosystems (PIE) LTER has, since its inception in 1998, been working towards a predictive understanding of the long-term response of coupled land-estuary-ocean ecosystems to changes in three drivers: climate, sea level, and human activities. The Plum Island Estuary-LTER includes the coupled Parker, Rowley, and Ipswich River watersheds, estuarine areas including a shallow open sound, and extensive tidal marshes. PIE is connected to the Gulf of Maine in the Acadian biogeographic province, which is a cold water, macrotidal environment that is geographically and biologically distinct from coastal ecosystems to the south of Cape Cod, Massachusetts. Over the next four years the LTER will build upon the progress they have made in understanding the importance of spatial patterns and connections across the land-margin ecosystem. The overarching goal is to understand how external drivers, ecosystem dynamics, and human activities interact to shape ecological processes in a mosaic of coastal landscapes and estuarine seascapes. Understanding how landscapes and seascapes evolve and change, and how those changes control ecosystem processes, is both a fundamental science question and a critical management question. During the remainder of PIE III LTER researchers will continue to address the role of temporal change and variability in climate, sea-level rise and human activities on ecological processes in our long-term monitoring but they will also initiate new activities that examine spatial arrangements and connectivity. LTER research questions are focused around two themes: 1) What controls the spatial arrangements and connectivity between ecological habitat patches in the coastal zone? 2) How do the spatial arrangement and the connectivity between ecological habitat patches in coastal watersheds and the estuarine seascape influence ecological processes? NSF OCE LTER-PIE: Interactions Between External Drivers, Humans and Ecosystems in Shaping Ecological Process in a Mosaic of Coastal Landscapes and Estuarine Seascapes